Clinical and virological features of Dengue in Vietnamese infants. - Tran Nguyen Bich Chau; Katherine L Anders; Le Bich Lien; Nguyen Thanh Hung; Lu Thi Minh Hieu; Nguyen Minh Tuan; Tran Thi Thuy; Le Thi Phuong; Nguyen Thi Hong Tham; Mai Ngoc Lanh; Jeremy J Farrar; Stephen S Whitehead; et al. (Public Library of Science (PLoS), 2010)
Infants account for a small proportion of the overall dengue case burden in endemic countries but can be clinically more difficult to manage. The clinical and laboratory features in infants with dengue have not been extensively characterised.This prospective, cross-sectional descriptive study of infants hospitalized with dengue was conducted in Vietnam from November 2004 to December 2007. More than two-thirds of 303 infants enrolled on clinical suspicion of dengue had a serologically confirmed dengue virus (DENV) infection. Almost all were primary dengue infections and 80% of the infants developed DHF/DSS. At the time of presentation and during hospitalization, the clinical signs and symptoms in infants with dengue were difficult to distinguish from those with other febrile illnesses, suggesting that in infants early laboratory confirmation could assist appropriate management. Detection of plasma NS1 antigen was found to be a sensitive marker of acute dengue in infants with primary infection, especially in the first few days of illness.Collectively, these results provide a systematic description of the clinical features of dengue in infants and highlight the value of NS1 detection for diagnosis.